ANALISIS PREDIKSI SEBARAN ALAMI GAHARU MARGA Aquilaria DAN Gyrinops DI INDONESIA - Roemantyo Roemantyo; Tukirin Partomihardjo (Research Center for Biology-Indonesian Institute of Sciences, 2010)
A spatial analysis was applied to predict the natural distribution of agarwood producing taxa of Aquilaria and Gyrinops in Indonesia.This research was conducted using herbarium materials which deposited in Hebarium Bogoriense, Research Center for Biology-LIPI and field data collected by researcher within periods of 1992-2009. Time serial maps of 1:250.000 were used in this analysis such as Indonesia digital base map of 1990, province land cover and deforestation digital maps of 1989 and 2005.Every sites of herbarium collection was identified using digital Cyclopedia of Malesian Collectors for the name of village/place and date of collection. The coordinate of those sites comprises latitude, longitude and altitude was retrieved by query method using Indonesia digital geo-reference data. Tabulated data of every collection/data was created and then overlaid to the time serial land cover and deforestation maps using GIS software, to identify the recent condition of that area. The results show that horizontal natural distribution of Aquilaria was mainly occur in the western part of Indonesia, while Gyrinops in eastern part of Indonesia. Vertical distribution analyses of the Aquilaria and Gyrinops showed that in general both genera are mainly grown naturally in the low land areas less than 300 m asl. Spatial analyses using time serial land cover and deforestation maps indicated that low land areas less than 300 m asl. having very high risk on the land use changes, whereas increasing land status classification from six on 1989 to fifteen on 2005. More than 20 % of forested areas have been change into non forest area such as plantation, agricultural land, resettlements and open unproductive lands since 1989. Natural distribution of agarwood producing taxa horizontally and vertically on all of major islands and the conservation strategy were discussed in this paper.